Analisis Pendekatan Humanisme dalam Pembelajaran Kurikulum Merdeka: Dampaknya Terhadap Karakter Mandiri Siswa Sekolah Dasar - Hidayat, Wahyu; Wijaya, Khairil Candra; Rahmatsyah, Rahmatsyah; Ramadhani , Nurul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to explore the reflection of the application of the philosophy of Humanism in the learning process and its impact on the development of independent character of elementary school students. The philosophy of Humanism, which emphasizes the importance of individual potential, personal experience, and self-actualization, is applied in educational contexts to create learning environments that support students’ holistic development. The research method used is a descriptive qualitative approach. This research is located at SD Unggulan Aisyiyah Ngemplak Sleman Data was collected through class observation, interviews with teachers and students, and analysis of learning documents. The results showed that the application of the principles of Humanism in learning, such as student-centered learning, respect for individuality, and the creation of an empathetic and supportive learning environment, has a significant positive impact on the development of students’ independent character. Students who learn in an environment that supports and values their individuality show improvements in self-confidence, decision-making skills, and independent learning abilities. They are also better able to explore creativity and develop good social skills. This study concludes that the application of the philosophy of Humanism in elementary school learning not only improves students’ academic achievement but also strengthens their independent character. These findings provide important implications for educators and education policymakers in designing more holistic and student-centered curricula and learning methods. Thus, the Humanism approach in basic education can be an effective strategy to prepare young people who are independent, creative, and ready to face future challenges.